Child and adolescent psychopathy: Assessment issues and treatment needs - Silva, Diana Ribeiro da (2013)
The identification of psychopathic traits in childhood and adolescence is a topic of growing interest for scientific research. The development of models to predict violent behavior, together with efficient preventive and therapeutic programs, is a major goal when assessing youths with psychopathic traits. This paper focuses on the construct of child and adolescent psychopathy, while approaching historical and conceptual issues. By discussing the “state of the art” of the construct, we will analyze different instruments to assess psychopathy in children and adolescents, as well as the available treatment modalities. Finally, we will present possible lines for research and clinical intervention according to an evolutionary approach to anger and antisocial behavior.